PENGARUH MODEL PEMBELAJARAN “TWO STAY TWO STRAY” TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS V SD IT AL-MUNAWWAR - Nadya Annisa Lubis; Rahmi Seri Hanida; Sahyoni (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to determine the effect of the two stay, two stray learning model on the social studies learning outcomes of fifth-grade students at Al-Munawar Islamic Elementary School. The type of research used in this study is experimental research (experiment research). The research design used in this study is a quasi-experiment design in the form of a nonequivalent control group design. The experimental class is the class that receives treatment in the form of the